Outcome of non-surgical dietary treatment with or without lactulose in dogs with congenital portosystemic shunts. (1st January 2020) - Favier, Robert P.; de Graaf, Eline; Corbee, Ronald J.; Kummeling, Anne
Abstract: Background: Congenital portosystemic shunts (CPSS) are vascular anomalies, allowing portal blood to bypass the hepatic parenchyma, thereby accumulating toxic substances such as ammonia in the systemic circulation resulting in hepatic encephalopathy. Aim: To evaluate the outcome of non-surgically treated dogs with a CPSS. Methods: Case records of 78 dogs with a single congenital CPSS confirmed by ultrasound and/or computed tomography between September 2003 and February 2015 were reviewed. Median age at diagnosis of CPSS in dogs was 10.8 months (range 2–133 months). Non-surgical treatment was started as an adjusted diet (a diet restricted in protein) with or without lactulose. Owners were contacted by telephone to determine survival time and presumed cause of death, if applicable. In addition, a questionnaire was used to retrospectively assess quality of life (QoL) and CPSS scores in 37 dogs before and during non-surgical treatment. Differences between Kaplan–Meier curves were tested by a Log rank test. Results: Overall estimated median survival time (EMST) was 38.5 months (range 1 day − 91 months; 78 dogs). No significant differences between EMSTs were found between dogs with extra- ( n = 48) or intrahepatic ( n = 29) shunts, nor between treatment with only an adjusted diet, or an adjusted diet combined with lactulose. During non-surgical treatment, significant improvement in perceived QoL and CPSS scores were found ( P < 0.01). Conclusion: Our study demonstrated that an overall median EMST of 3.2 years was reached and that owners retrospectively perceived that non-surgical treatment resulted in an improved QoL and clinical performance, irrespective of intrahepatic or extrahepatic CPSS location.